SEROPREVALENCE AND RISK FACTOR OF TOXOPLASMOSIS IN SCHIZOPHRENIA PATIENTS REFERRED TO GRHASIA PSYCHIATRIC HOSPITAL, YOGYAKARTA, INDONESIA - Muflikhah, Nina Difla; Supargiyono, Supargiyono; Artama, Wayan Tunas (African Journal of Infectious Diseases (AJID), 2018)
Background: Toxoplasmosis is an infectious disease caused by protozoan parasite called Toxoplasma gondii. Toxoplasma gondii is an intracellular protozoan parasite belong to phylum Apicomplexa, is an obligate parasite in mammals. The active proliferating trophozoites or tachyzoites are usually seen in the acute stage of infection, while the resting bradyzoites formed tissue cysts are primary found in muscle and brain. Human infection occurs mainly by ingesting food or water contaminated with oocyst or eating an undercook meat containing tissue cyst. Human might be infected via blood transfusion, organ transplantation or transplacenta transmission. Schizophrenia is a complex neuropsychiatric disease of the central nervous system, which contributing to behavioral changes which may resulted in higher risk to T. gondii infection. The purpose of this study were to know difference of seroprevalence and risk factor of toxoplasmosis between schizophrenia group and control group.Materials and Methods: Serum sample were collected 94 among schizophrenia patient at Grhasia Hospital and 64 normal population (control group). Antibody IgG of T. gondii was measured using ELISA method (Enzym Link Immnusorbent Assay) and questionnaires were used to collect risk factor data among the respondent.Results: The seroprevalence antibody IgG of patient with schizophrenia (69.14%) higher than control group (65.625%), but not significantly different (p>0.05). There was an association between some of risk factor with seropositive of toxoplasmosis in both group. In schizophrenia group, risk factor that associated with toxoplasmosis are uncooked meat consumption, contact with uncooked meat and soil, handwashing habit, uncooked water consumption, and water source. In control group, risk factor that associated are having cattles/pet, undercook meat consumption, and water source. Conclusion: This finding have shown seroprevalence of schizophrenia group higher than non-schizophrenia group and risk factor which associated with toxoplasmosis was different between two groups.